1983
DOI: 10.1159/000265260
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic Complement in Tears

Abstract: We performed hemolytic assays for C1, C4, C3 and C5 on tear samples from 7 normal subjects and 10 patients with corneal ulcers. Hemolytic activities in tears were determined by 50% hemolysis of sensitized sheep red blood cells. Absent or low hemolytic activities of C1, C4 and C3 were found in normal tears. C5 was detected in tear samples from 4 of 7 normal subjects. Tear samples from patients with corneal ulcers showed elevated levels of C1, C4, C3 and C5, but wide ranges in values were found. C5 had the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…obs.). This is comparable with levels of 6.25–12.5% serum complement haemolytic activity reported in normal human tears, which is another site of mucosal immunity 34 …”
Section: Haemolytic Assay Of Breast Milk Complement Activitysupporting
confidence: 86%
See 1 more Smart Citation
“…obs.). This is comparable with levels of 6.25–12.5% serum complement haemolytic activity reported in normal human tears, which is another site of mucosal immunity 34 …”
Section: Haemolytic Assay Of Breast Milk Complement Activitysupporting
confidence: 86%
“…Mucosal complement secretion and activities are known to increase in states of infection or other inflammatory disorders of the mucosal membranes, including mastitis in the mammary gland, microbial corneal ulcers and conjunctivitis in the eye, chronic inflammatory bowel diseases of the intestine and inflammatory nephritides 34 , 42 , 43 , 49 , 50…”
Section: Physiological Significance Of Mucosal Complementmentioning
confidence: 99%
“…However, a considerable body of evidence had shown that in cases of inflammation, complement protein levels in ocular fluids were elevated and in some cases approached those found in serum. 24,[34][35][36][37] It should be kept in mind that antiglaucoma drugs delivered on the ocular surface diffuse from the tear film to the trabecular meshwork, directly through conjunctival and scleral pathways or indirectly through transcorneal route. As a consequence, drugs encounter the complement system in tears, cornea, posterior sclera and aqueous humor, where complement proteins are similar to those in plasma although less concentrated.…”
Section: Discussionmentioning
confidence: 99%
“…Complement C3, clearly found to be decreased by taurine application, activates the complement cascade and was documented to be the major player in closed eye tear inflammatory processes [71]. Since complement C3 was reported to develop hemolytic activity in tears [72,73] a potentially taurine depending downregulation could be associated with the observed level decrease of haptoglobin related protein and hemopexin, which are both anti-oxidant protective plasma proteins playing an important role in inflammatory hemolysis [74][75][76][77][78]. Regarding the classes of candidate proteins it can be suggested that the taurine impact is predominantly focused on proteins occurring in the course of inflammation and hemolysis, whereby several of these proteins are known to play a role in dry eye and related diseases.…”
Section: Discussionmentioning
confidence: 99%